Safety of high power and short duration ablation (70 watts over 5–7 seconds) in patients with persistent atrial fibrillation undergoing pulmonary vein isolation and additional substrate modification. (14th October 2021) - Bartkowiak, M; Kottmaier, M; Reents, T; Bourier, F J; Telishevska, M; Koch-Buettner, K; Risse, E; Maurer, S; Krafft, H; Popa, M A; Otgonbayar, U; Lennerz, C; et al.
Abstract: Background: In paroxysmal atrial fibrillation (AF), pulmonary vein isolation using HPSD has shown a promising success rate compared to ablation using conventional power settings, as well as a significant reduction in procedural and ablation time. In persistent atrial fibrillation, left atrial substrate modification seems to be a promising additional ablation approach besides pulmonary vein isolation (PVI). However, results after additional substrate ablation are not consistently positive, which may be related to non-transmural lesions and tissue oedema. An extended time of the procedure may also influence safety. Recent publications showed that HPSD ablation provides more sufficient lesions due to acute cell necrosis instead of cell oedema. Purpose: The aim of this study is to evaluate the safety of HPSD ablation in patients undergoing ablation of persistent atrial fibrillation with PVI and additional substrate modification. Methods: We studied and compared n=300 patients from our register undergoing the first ablation of persistent atrial fibrillation with HPSD settings (n=150) between May 2018 and January 2019 and standard settings (n=150) between July 2017 and January 2018. Patients were followed up for three months to report procedure-related adverse events. In all patients, a modified stepwise approach using PVI followed by electrogram-guided substrate modification and linear-ablation, if necessary, was performed. A HPSD ablation was performed with 70 watts with a maximum duration of 5–7 seconds. Catheter irrigation was set to 20 ml/min using the Flexability™ ablation catheter and the Ampere™ generator. The patients were compared with a historical cohort that underwent PVI using a conventional power protocol with 30–40 watts over 20–40 seconds, using the same ablation catheter. A transthoracic echocardiogram was performed in all patients after the ablation-procedure and on the following day. Duplex sonography or clinical control were performed to assess groin complications. Results: Baseline characteristics and procedural data are shown in table 1. No significant difference in the complication rates in both groups was observed by a significant procedure-time reduction in HPSD-Group (2:13h vs 2:31h p<0, 001) and overall low risk of the procedure. No deaths, thromboembolic complications or atrioesophageal fistula were registered. Complication rates with statistical relevancy are shown in table 2. Conclusion: Complex ablation using PVI and additional substrate modification in persistent atrial fibrillation using HPSD seems to be equally as safe regarding procedure-related outcomes as standard power settings ablation and can significantly reduce the time of the overall procedure. Funding Acknowledgement: Type of funding sources: None.